PENGENALAN: PENGOLAHAN SAMPAH ORGANIK BERBASIS â€œECO-ENZYMEâ€ DI DESA BATANNYUH, MARGA, TABANAN - Anak Agung Komang Suardana; Ni Putu Nensy Aryanti Rahayu (JURNAL SEWAKA BHAKTI, 2021)
Community service entitle Introduction: "Eco-Enzyme" Based Organic Waste Processing in Batannyuh Village, Marga, Tabanan. This program involves the Women Farmers Group "Bakti Pertiwi" in collaboration with the 2021 Universitas Hindu Indonesia Students which located in Batannyuh Village, Marga, Tabanan. The purpose of this service activity is to provide an understanding of "Eco-Enzyme"-Based Organic Waste Processing. It is expected that the understanding of the "Eco-Enzyme" process can be used as a reference in processing organic waste in Batannyuh Village, Marga, Tabanan. The introduction of this program was carried out online with the Women Farmers Group "Bakti Pertiwi" and KKNT students at Universitas Hindu Indonesia. The conclusion of this service program is the importance of processing organic waste. The remnants of organic waste that have been considered useless, in fact store bioactive materials that can be used for various purposes. The introduction of "Eco-Enzyme"-based organic waste processing is only a theory so it needs to be practiced more realistically so that the benefits are more felt by the community, especially the "Bakti Pertiwi" group and then be disseminated to the community in Batannyuh Village, Marga, Tabanan